Coach-led prevention programs are effective in reducing anterior cruciate ligament injury risk in female athletes: A number-needed-to-treat analysis - Pfile, K. R.; Curioz, B. (Scandinavian Journal of Medicine & Science in Sports, 2017)
The purpose of this study was to determine whether the effectiveness of an anterior cruciate ligament (ACL) prevention program is impacted by the individual(s) directing the program. A number-needed-to-treat analysis compared the effectiveness of injury prevention measures when either directed by a coach or a mixed leadership group consisting of coach and healthcare providers. Eleven studies were included for analysis. Number-needed-to-treat and relative risk reduction (RRR) were calculated for each study and data sets were pooled based on the intervention leader. Quality of evidence was determined by assessing individual studies (PEDro score math formula=4.55±1.97, range=2-7), applying the Oxford Centre for Evidence-Based Medicine Levels of Evidence (CEBM=2a), and the Strength of Recommendation Taxonomy (SORT=Level B). The mixed leadership group studies' RRR=48.2% (95% confidence interval (CI)=22-65) and a number-needed-to-benefit of 120 (CI=73-303) while the coach-led group's RRR=58.4% (CI=40-71) and a number-needed-to-benefit=133 (CI=96-217). These results demonstrate that a coach-led ACL injury prevention program approach is as effective as a mixed group leadership approach. Coach-led prevention programs can be more widely implemented; however, it is imperative to ensure adequate training is in place prior to implementation of such intervention.